Penggunaan Pertamax Sebagai Modifier Pada Lasbutag Campuran Dingin Untuk Perkerasan Jalan - Alamsyah, Alik Ansyori (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2011)
This research is to know there are any influences of variation modifier to marshall like Stability, Flow, Marshall Quotient, and Air Void. And ideal variation mixture of Asbuton by using Pertamax as modifier.by using rate pave oil 2%, 2,2 %, 2,4%, 2,6%, 2,8%, and 3% , made object test counted 3 x 6 test object ( for statistical test) which in form of volume weighing cylinder 1200 grams. variation of Modifier total which used in this research are 3,75%, 3,85%, 3,95%, 4,05%, 4,15%, and 4,25% and for the each of - variation modifier use 3 test object. Stability of Marshall will reach under conditions at usage of total modifier 3,83% and will reach conditions of maximal at usage of total modifier 4,68%. From variation of modifier fulfilling conditions of SNI-06-2489-1991 Lasbutag Cold Mix for the Stability , Flow, Air Void and Marshall Quotient which have been known, can be calculated ideal modifier for the Lasbutag Cold Mix that is ± 4,10%.Keyword : Pertamax, Lasbutag, cold mix